THE INFLUENCE OF SOCIAL FACTORS ON THE STATE OF HEALTH OF ADOLESCENTS (Regional aspects of productive forces development of Ukraine, 2024)
Introduction. The relevance of this study is determined by the increasing impact of social factors on the health of adolescents in modern society, especially in Ukraine under wartime conditions. Adolescence is a critical period for the formation of physical and mental health, and during this time, individuals are most vulnerable to external influences. The social environment, including family, peers, mass media, and social networks, significantly affects the well-being and development of adolescents. Analyzing these factors is crucial for developing effective strategies to support the health of the younger generation, which in turn will contribute to the formation of a healthy nation in the future.The purpose of the article is a theoretical and methodological analysis of the influence of various social factors on the physical and mental health of adolescents with the aim of developing scientifically-based recommendations for improving their health through the implementation of effective social programs and policies.Methods. To achieve the research objectives, a comprehensive approach was used, including: analysis of scientific literature on the impact of social factors on adolescent health; comparative analysis of the impact of various social factors on adolescent health; statistical analysis to identify the most significant social factors and their impact on adolescent health.Results. The study assessed the most important factors affecting health preservation in adolescence. Each of these factors was detailed, including their direct impact on the adolescent's psyche and consciousness. Particular attention was paid to aspects such as family environment, peer relationships, academic load, access to medical services, and the level of physical activity.The family environment is considered a fundamental factor shaping the foundations of healthy adolescent development. The role of parents in maintaining emotional stability, the importance of positive family relationships, and the impact of the family's economic status on access to quality medical services and healthy nutrition are highlighted.Peer relationships are characterized as an important social factor that can both benefit and harm the adolescent's health. Positive relationships provide support and contribute to the development of healthy social skills, while negative social experiences, such as bullying, can lead to stress and depressive states.Academic load is also considered an important factor affecting the mental health of adolescents. It is emphasized that high demands and pressure from educational institutions can cause chronic stress, negatively impacting overall well-being and mental health.Access to medical services and the level of physical activity are important factors for physical health. It is described how insufficient access to medical services can lead to the untimely detection and treatment of diseases, and low levels of physical activity can lead to weight problems and other physical ailments.Recommendations for parents on how to help overcome the challenges of adolescence are provided. The advice includes building trusting relationships with children, providing emotional support, monitoring the adolescent's social circle, reducing academic load through organizing an effective daily routine, encouraging physical activity, and timely consultation with medical specialists. Parents are also encouraged to actively participate in their children's lives, providing them with a safe and supportive environment for comprehensive development.